2021
DOI: 10.1111/jfpp.15876
|View full text |Cite
|
Sign up to set email alerts
|

Acorn and water interactions on the microstructure of gluten‐free yeasted dough

Abstract: Gluten-free doughs were prepared by replacing part of a dry mixture of rice flour and corn starch with acorn meal (5%-25%) at different levels of water (65%-75%). The changes in dough microstructure were investigated using of X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and Scanning electron microscopy, whereas the physicochemical properties by hydration tests. There were significant differences in physicochemical properties such as water-abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[ 24 ] The diffraction peak area at 15.0°, 17.0°, 18.1°, and 23.0° increased from acorn flour to de‐polyphenolized acorn flour and then to acorn starch, indicating that the de‐phenolization and extraction of acorn starch slightly changed the crystalline structure of starch, but not the crystal type, which is consistent with the results of a previous study. [ 25,26 ] It has also been reported that the original crystal type of waxy corn starch was not altered by debranching, and the increase in the RC was correlated with the increase in the debranching degree. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] The diffraction peak area at 15.0°, 17.0°, 18.1°, and 23.0° increased from acorn flour to de‐polyphenolized acorn flour and then to acorn starch, indicating that the de‐phenolization and extraction of acorn starch slightly changed the crystalline structure of starch, but not the crystal type, which is consistent with the results of a previous study. [ 25,26 ] It has also been reported that the original crystal type of waxy corn starch was not altered by debranching, and the increase in the RC was correlated with the increase in the debranching degree. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…Capron et al (2007) reported that the ratio of 1047 cm −1 to 1017 cm −1 (ratio 1) is used to determine the alignment of helices within the short-range order influenced by the presence of water molecules that are bonded to the starch molecules. The ratio of 995 cm −1 to 1022 cm −1 (ratio 2)) is a widely used parameter for assessing starch's double helices and short-range structure (Figure 7b) [43]. In ratio 1, samples D-0, D-25, and D-50 had similar AUC values (p > 0.05).…”
Section: Ftir Analysis Of Doughmentioning
confidence: 99%
“…Because of its gluten‐free and nutritious composition, the utilization of acorn flour has recently been investigated in both gluten‐free and gluten‐containing formulas (Amina et al., 2018 ; Papoti et al., 2018 ; Sasani et al., 2023 ). Among the various species, the carbohydrate, fiber, protein, fat, and mineral values of acorn have been determined to be in the ranges of 41.52%–78.83%, 13.11%–51.76%, 2.08%–4.94%, 0.76%–3.08%, and 1.78%–3.21%, respectively (Skendi et al., 2022 ). Furthermore, acorn contains oleic (more than 50%), linoleic, and palmitic acids, besides containing phenolics and essential amino acids.…”
Section: Introductionmentioning
confidence: 99%